Psychological and pedagogical principles of building a business game in the educational process (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the psychological and pedagogical principles, which illustrate the constituent parts, the logic and internal relationships of the business game. Each principles is to complement and develop others they create the concept of gaming as a form of active learning.
Keywords: business game; psychological and pedagogical principles of dialogue